Tackling Forced Labour in Supply Chains: The Brazilian Case - Harada Mirra, Margarida Maria (Center for Law and Responsible Business Studies, 2025)
Despite the global prohibition of slavery and the widespread implementation of legal frameworks to combat forced labour, this illegal practice remains widespread, particularly in complex global supply chains. Given this worrying scenario, exacerbated by the expansion of cross-border manufacturing, this study critically examines the effectiveness of existing laws in addressing forced labour in supply chains, with a particular focus on international legal instruments and Brazil’s anti-slavery legislation. Brazil was chosen as a case study due to its comprehensive and robust legal framework against forced labour, but persistent incidence of modern slavery cases. Using the traditional research method, this paper conducts a conceptual and theoretical analysis of Brazilian anti-slavery laws, incorporating an examination of relevant international and national legislation, case law and treaties. By examining the Brazilian case study, this article aims to provide valuable insights for other developing countries facing similar challenges. It demonstrates that modern slavery persists in environments where legal enforcement is weak, public institutions are ineffective, and institutional support is lacking.